2015
DOI: 10.1007/s10965-015-0743-1
|View full text |Cite
|
Sign up to set email alerts
|

One pot fabrication of optically active and efficient antibacterial poly(amide-benzimidazole-imide)/Ag bionanocomposite

Abstract: Poly(amide-benzimidazole-imide) (PABI) containing silver nanoparticles was fabricated through in situ procedure using DMF as a common solvent which leads to spontaneous slow reduction at ambient temperature. UV/vis technique verified silver nanoparticles formation in the polymer matrix. The silver nanoparticles presence was also confirmed using various characterization techniques and their dispersion was verified by microscopic studies (TEM and FE-SEM analysis) which revealed good dispersion of Ag nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, the signal is faint, most likely because the CR−Ag NPs are distributed throughout the polymer matrix. Additionally, the EDX profile of the produced polymer nanocomposites exhibits signals related to oxygen, which may have been generated by the embedded CR−Ag NPs [48] . From the above observations, it is clear that the modification of PVA by the inclusion/incorporation of CR−Ag NPs is significant and is supported by the existing elements on the CR−Ag PVA films.…”
Section: Resultsmentioning
confidence: 84%
“…However, the signal is faint, most likely because the CR−Ag NPs are distributed throughout the polymer matrix. Additionally, the EDX profile of the produced polymer nanocomposites exhibits signals related to oxygen, which may have been generated by the embedded CR−Ag NPs [48] . From the above observations, it is clear that the modification of PVA by the inclusion/incorporation of CR−Ag NPs is significant and is supported by the existing elements on the CR−Ag PVA films.…”
Section: Resultsmentioning
confidence: 84%
“…Results showed that these NPs not only can generate a stronger signal than the usually used gold nanorods and single-walled carbon nanotubes on a per mass basis but also they are an ideal nanoplatform for enhancing photoacoustic molecular probes. Mallakpour et al [92] synthesized poly (amide-benzimidazole-imide) (PABI) nanostructure containing amino acid. FE-SEM images showed nano-patterns of PABI particles with homogenous spherical shape.…”
Section: Application Of Other Class Of Nanostructure Polymersmentioning
confidence: 99%
“…Hence, alternative approaches are needed to strengthen the antifungal pipeline . In recent years, nanomaterials have been used to form novel antimicrobial agents with distinctive chemical and physical properties. , Nanomaterials like silver (Ag), , zinc oxide (ZnO), titanium dioxide (TiO 2 ), iron oxide (Fe 3 O 4 ), copper oxide (CuO), magnesium oxide (MgO), and nitric oxide (NO) nanoparticles have displayed antibacterial activity. However, their toxicity has proven to be challenging for applications in the biomedical field…”
Section: Introductionmentioning
confidence: 99%